how do you do this?? -4x-7=-2(x+3)

-4x-7=-2(x+3) Multiply -2 by each term inside the parenthesis (x+3). -4x-7=(-2(x)-2(3)) Complete the multiplication of -2 by each term inside the parenthesis. -4x-7=(-2x-6) Remove the parenthesis around the expression -2x-6. -4x-7=-2x-6 Since -2x contains the variable to solve for, move it to the left-hand side of the equation by adding 2x to both sides. -4x-7+2x=-6 Since -4x and 2x are like terms, subtract 2x from -4x to get -2x. -2x-7=-6 Since -7 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 7 to both sides. -2x=7-6 Subtract 6 from 7 to get 1. -2x=1 Divide each term in the equation by -2. Simplify the left-hand side of the equation by canceling the common terms. Simplify the right-hand side of the equation by simplifying each term. therefore x = -1/2

First Name

Your Response